Introduction to international disaster management - Coppola, Damon P. (Boston : Butterworth-Heinemann, 2011)
Written from a global perspective on risk, hazards, and disasters, Introduction to International Disaster Management provides practitioners, educators and students with a comprehensive overview of the players, processes and special issues involved in the management of large-scale natural and technological disasters. The book discusses special issues encountered in the management of international disasters, and explains the various private, non-governmental, national, and international agencies that assist in preparedness, mitigation, response and recovery during national and regional events. Concentrating on the four major phases of emergency management - mitigation, preparedness, response, and recovery - Introduction to International Disaster Management deals with such timely topics as Hurricane Katrina, the 2004 Asian tsunami, and SARS. It also serves as a reference to governmental and other agencies involved in international disaster management activities. This book is the first of its kind to take a global approach to the topic of international disaster management. * Data, discussions, and outcomes for recent major and catastrophic disasters including Cyclone Nargis, earthquakes in Yogyakarta, China, Pakistan, and Chile, the H1N1 pandemic, and the tsunami in American Samoa * Added material on hazards, catastrophic risk management, mitigation, and disaster myths * Expanded sections on public disaster preparedness and disaster recovery best practices * Commentary on the latest research in disaster management and policy studies.
Chapter 1: The Management of Disasters -- Chapter 2: Hazards -- Chapter 3: Risk and Vulnerability -- Chapter 4: Mitigation -- Chapter 5: Preparedness -- Chapter 6: Response -- Chapter 7: Recovery -- Chapter 8: Participants -- Governmental Disaster Management Agencies -- Chapter 9: Participants -- Nongovernmental Organizations -- Chapter 10: Participants -- Multilateral Organizations and the International Financial Institutions -- Chapter 11: Special Considerations.
Includes index.
Keywords: Disaster relief -- International cooperation; Emergency management -- International cooperation; Hazard mitigation; Disaster relief -- International cooperation; Emergency management -- International cooperation; Hazard mitigation; Electronic books